Confucian Political Ethics - Bell, Daniel (Daniel A.), 1964- (Book collections on Project MUSE., 2008)
Drawing upon in-depth, cross-cultural dialogues, the contributors delve into the relationship of Confucian political ethics to contemporary social issues, exploring Confucian perspectives on civil society, government, territorial boundaries and boundaries of the human body and body politic, and ethical pluralism. They examine how Confucianism, often dismissed as backwardly patriarchal, can in fact find common ground with a range of contemporary feminist values and need not hinder gender equality. And they show how Confucian theories about war and peace were formulated in a context not so different from today's international system, and how they can help us achieve a more peaceful global community. --From publisher's description.